Utopian disjunctures: Popular democracy and the communal state in urban Venezuela. (March 2017) - Wilde, Matt
This article examines the Venezuelan government's efforts to establish a 'communal state' through the eyes of working-class chavista activists in the city of Valencia. It argues that the attempt to incorporate grassroots community organisations into a state-managed model of popular democracy produces a series of 'utopian disjunctures' for the actors involved. These disjunctures, the article contends, stem from conflicting political temporalities within the chavista project, as long-term aspirations of radical democracy clash with more short-term demands to obtain state resources and consolidate the government's power. The case highlights the tensions generated by efforts to reconcile radical democratic experiments with left-nationalist electoral politics.